Gain enhancement in L-band EDFA through a double-pass technique - Harun, Sulaiman Wadi; Poopalan, Prabakaran; Ahmad, Harith (Institute of Electrical and Electronics Engineers (IEEE), 2002)
An improvement of gain in the long-wavelength band (L-band) is observed by double passing the forward amplified spontaneous emission and signal in the erbium-doped fiber (EDF) using a circulator, unlike the conventional single pass amplification. A gain enhancement as high as 11 dB is obtained for a 1570-nm signal with an input power of -20 dBm at 98 mW of pump power. However, a noise figure penalty of about 2 dB is observed.